2022
DOI: 10.3389/fpsyt.2021.752874
|View full text |Cite
|
Sign up to set email alerts
|

Social Robots for Supporting Post-traumatic Stress Disorder Diagnosis and Treatment

Abstract: Post-Traumatic Stress Disorder (PTSD) is a severe psychiatric disorder with profound public health impact due to its high prevalence, chronic nature, accompanying functional impairment, and frequently occurring comorbidities. Early PTSD symptoms, often observed shortly after trauma exposure, abate with time in the majority of those who initially express them, yet leave a significant minority with chronic PTSD. While the past several decades of PTSD research have produced substantial knowledge regarding the mec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 102 publications
0
8
0
Order By: Relevance
“…The authors explain that social robots could support people to get into therapy and maximize the effectiveness of the therapy by increasing the patients' engagement and continuing the support outside the therapy session. In a previous paper (53) we addressed similar benefits of using social robots for diagnosing and treating people suffering from posttraumatic stress disorder (PTSD), social robots can assist with overcoming several logistical and social barriers that trauma survivors face when required to monitor symptoms and when seeking mental health interventions.…”
Section: Social Robots For Well Beingmentioning
confidence: 99%
“…The authors explain that social robots could support people to get into therapy and maximize the effectiveness of the therapy by increasing the patients' engagement and continuing the support outside the therapy session. In a previous paper (53) we addressed similar benefits of using social robots for diagnosing and treating people suffering from posttraumatic stress disorder (PTSD), social robots can assist with overcoming several logistical and social barriers that trauma survivors face when required to monitor symptoms and when seeking mental health interventions.…”
Section: Social Robots For Well Beingmentioning
confidence: 99%
“…Nevertheless, our results also stress that the discussion theme has no meaningful nor significant effect on the way people perceive Pepper and the interaction. These preliminary results provide important evidence concerning the potential of introducing social robots in real-life applications for long-term use and establishing meaningful relationships with these agents over time (see [8]).…”
Section: Discussionmentioning
confidence: 81%
“…Social robots hold great potential for delivering or improving psycho-social interventions [7], supporting mental health [52], monitoring symptoms of chronic psychopathologies [53], aiding rehabilitation [30] and providing much-needed physical and social support across a number of daily life settings [1]. For example, a previous study by Nomura and colleagues [54] showed the benefits of employing social robots for minimising social tensions and anxieties, describing that participants with higher social anxiety tended to feel less anxious and demonstrate lower tensions when knowing that they would interact with robots in opposition to humans.…”
Section: Social Robots For Well Beingmentioning
confidence: 99%
“…The authors explain that social robots could support people to get into therapy and maximize the effectiveness of the therapy by increasing the patients' engagement and continuing the support outside the therapy session. In a previous paper [53] we addressed similar benefits of using social robots for diagnosing and treating people suffering from post-traumatic stress disorder (PTSD), social robots can assist with overcoming several logistical and social barriers that trauma survivors face when required to monitor symptoms and when seeking mental health interventions.…”
Section: Social Robots For Well Beingmentioning
confidence: 99%